2019
DOI: 10.1002/qua.25920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aluminum vacancies on the H2O2 or H2O interaction with a gamma‐AlOOH surface. A solid‐state DFT study

Abstract: The adsorption of a single H 2 O 2 or H 2 O molecule on a family of periodic slab models of γ-AlOOH is studied by solid-state DFT. The single H 2 O 2 or Н 2 О molecule interacts with the perfect (010) slab by intermolecular hydrogen bonds (H-bonds). In the models of γ-AlOOH with oxygen and aluminum vacancies, H 2 O 2 or Н 2 О also forms covalent OÁÁÁAl bonds. The energies of covalent OÁÁÁAl and H-bonds are estimated by a combined approach based on simultaneous consideration of the total binding energies with B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 94 publications
1
4
0
Order By: Relevance
“…We would like to call for caution about possible cross-reactions between AH and H 2 O 2 used as positive control. Indeed, AH could adsorb H 2 O 2 limiting its oxidative capacity in living cells 58 and our results consistently suggested that AH could limit H 2 O 2 induced ROS production.…”
Section: Discussionsupporting
confidence: 79%
“…We would like to call for caution about possible cross-reactions between AH and H 2 O 2 used as positive control. Indeed, AH could adsorb H 2 O 2 limiting its oxidative capacity in living cells 58 and our results consistently suggested that AH could limit H 2 O 2 induced ROS production.…”
Section: Discussionsupporting
confidence: 79%
“…The enthalpies of H-bonds formed by H 2 O 2 as a proton donor turned out to be higher or comparable with the values of the corresponding H-bonds formed by H 2 O [ 15 , 32 , 43 ]. In the case of H-bonds formed by H 2 O 2 and H 2 O as a proton acceptor, the picture is reversed.…”
Section: Resultsmentioning
confidence: 92%
“…Comparison of enthalpies/energies of intermolecular H-bonds in crystals of organic molecules, in particular, crystalline peroxosolvates, obtained using approximations (1), (2), and (3) was carried out in a number of papers [13,[144][145][146]. Significant differences in the calculated values are observed only for short (strong) H-bonds [147], which are caused by the contribution of the covalent component to the energy of these bonds [148,149].…”
Section: The Energies Of Intermolecular Interactions Of H 2 O 2 In Organic Crystals: Calculations By the Kohn-sham Methods With Periodic mentioning
confidence: 99%